2018
DOI: 10.21162/pakjas/18.7036
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE TOLERANCE AND PHYTOSTABILIZATION POTENTIAL OF Conocarpus erectus AND Eucalyptus camaldulensis GROWN IN CADMIUM CONTAMINATED SOIL

Abstract: Phytoremediation is the most promising approach for the remediation of Cd contaminated soils. In the present study, Cd tolerance and phytoremediation potential of Conocarpus erectus and Eucalyptus camaldulensis, was evaluated in a pot experiment for a growth period of 6 months. Two-month-old plants of uniform size were transplanted in Cd-contaminated soil (0, 5, 10 and 15 mg kg-1), and their growth attributes, chlorophyll contents, root and shoot Cd concentration, bioconcentration factor (BCF) and translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…Different studies have reported up-regulation in the expression of enzymes synthesizing phenolic compounds (phenylalanine ammonia-lyase), as they act as antioxidant enzymes under stressful environments [60]. Our results are in accordance with the previous studies on P. × canescens and C. camphora species, in which the accumulation of soluble protein and soluble sugar was increased under Cd treatment [52,61,62].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Different studies have reported up-regulation in the expression of enzymes synthesizing phenolic compounds (phenylalanine ammonia-lyase), as they act as antioxidant enzymes under stressful environments [60]. Our results are in accordance with the previous studies on P. × canescens and C. camphora species, in which the accumulation of soluble protein and soluble sugar was increased under Cd treatment [52,61,62].…”
Section: Discussionsupporting
confidence: 92%
“…However, in this study, the reduction in the chl a, b and carotenoid contents was higher in the case of the M. alba and P. deltoides saplings as compared to C. erectus and S. cumini. In the previous studies on Populus nigra, Salix alba, Eucalyptus hybrid, Conocarpus erectus, Eucalyptus camaldulensis and Conocarpus lancifolius, similar decreases have been reported, where the chl a, b and carotenoid contents decreased in plants grown in Cd-contaminated soil [44,[49][50][51][52]. Therefore, based on the lowest reduction in the chl a, b and carotenoid contents observed in C. erectus, it can be assumed that C. erectus showed a higher tolerance against the given Cd treatment.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations